The importance of relationships to the availability of credit - Cole, Rebel A. (Journal of Banking & Finance, 1998)
In this article, I examine the effect of pre-existing relationships between a firm and its potential lender on the potential lender's decision whether or not to extend credit to the firm. I find that a potential lender is more likely to extend credit to a firm with which it has a pre-existing relationship as a source of financial services, but that the length of this relationship is unimportant. These findings provide empirical support for theories of financial intermediation positing that banking relationships generate valuable private information about the financial prospects of the financial institution's customer. The results also provide evidence that potential lenders are less likely to extend credit to firms with multiple sources of financial services, in support of the theory that the private information a financial institution generates about a firm is less valuable when the firm deals with multiple sources of financial services.